Heart of a Marionette: Understanding the Nature of Child Neglect and Abuse - Febyanti Soetrisno (Institute of Research and Community Outreach - Petra Christian University, 2019)
This creative project is an epistolary novel in form of a diary of a young girl named, Caroline Kusnadi, who is usually referred as Carol. She is a daughter of a family of four, whose parents are divorced. She writes her diary entries while trying to survive her mother’s and sister’s worsening mistreatments toward Carol even though they know Carol’s condition. In this creative work, I use child neglect and abuse my topic, and I propose to understand the nature of child maltreatments as my theme. With this, I can show the experiences of child neglect and abuse itself from the eyes of the victims. This story was created based on how Indonesia society does not pay sufficient attention and appropriate measures in protecting children’s rights. This would be shown on how Carol’s father, mother, and sister for not giving appropriate treatments for Carol who should have deserve more than she has. Keywords: child maltreatment, child neglect, child abuse, epistolary, realistic fiction, slice of life